Pelatihan Pembuatan Daur Ulang Minyak Jelantah Berbasis Ecogreen di Rumah Singgah Yatim dan Dhuafa Kota Banjarbaru - Chandra Chandra; Asrinawaty Asrinawaty; Ahmad Fauzan; Norsita Agustina (Jurnal Abdimas Kesehatan (JAK), 2020)
Cooking oil is a daily necessity used by housewives for cooking purposes, but basically the community does not yet know and realize that cooking oil that has not been used can be used as household products. Waste cooking oil waste if not managed properly will make the environment dirty and can pollute water and soil. To overcome this problem, innovation in the management of waste cooking oil is needed by involving the community so that waste can be utilized as a product of economic value.One potential of cooking oil waste is a high content of fatty acids so that it can be utilized as an environmentally friendly dish soap. On one hand, in general the community is not yet economically productive, it is difficult to foster an entrepreneurial spirit to create jobs. The method to be used in achieving the objectives is by providing training in recycling used cooking oil into an eco-green floor cleaning and dishwashing soap, entrepreneurship education, encouraging home industries, and helping with product marketing. So that it can improve the standard of living of fostered orphans and poor people and the surrounding community can create jobs, so that people's lives will be better.